Identification of lncRNA–miRNA–mRNA networks in circulating exosomes as potential biomarkers for systemic sclerosis - Sun, Xiaolin; Ding, Tiantian; Wang, Baoyue; Chang, Zhifang; Fei, Hongchang; Geng, Lixia; Wang, Yongfu (Frontiers in Medicine, 2023)
Objective: This study aimed to analyze potential biomarkers for systemic sclerosis (SSc) by constructing lncRNA–miRNA–mRNA networks in circulating exosomes (cirexos). Methods: Differentially expressed mRNAs (DEmRNAs) and lncRNAs (DElncRNAs) in SSc cirexos were screened by high-throughput sequencing and RT-qPCR. Analysis of differentially expressed genes (DEGs) was performed using DisGeNET, GeneCards, GSEA4.2.3, GO, and KEGG databases. ROC curves, analysis of correlation, and a double-luciferase reporter gene detection assay were used to analyze ceRNA networks and clinical data. Results: In this study, 286 DEmRNAs and 192 DElncRNAs were screened, among which 18 DEGs were the same as SSc-related genes. The main SSc-related pathways included ECM receptor interaction, local adhesion, platelet activation, and IgA production by intestinal immune network. A hub gene, COL1A1, was obtained by a protein–protein interaction (PPI) network, and four ceRNA networks were predicted through Cytoscape. The relative expression levels of ENST0000313807, NONHSAT194388.1, and COL1A1 were significantly higher in SSc, while the relative expression levels of hsa-miR-29a-3p, hsa-miR-29b-3p, and hsa-miR-29c-3p were significantly lower in SSc (p < 0.05). The ROC curve showed that the ENST00000313807-hsa-miR-29a-3p-COL1A1 network as a combined biomarker of SSc is more valuable than independent diagnosis, and this network correlated with HRCT, Scl-70, CRP, Ro-52, IL-10, IgM, lymphocyte percentage, neutrophil percentage, albumin divided by globulin, urea, and RDW-SD (P < 0.05). Double-luciferase reporter gene detection showed that ENST00000313807 interacts with hsa-miR-29a-3p, which interacts with COL1A1. Conclusion: The ENST00000313807-hsa-miR-29a-3p-COL1A1 network in plasma cirexos may be a potential combined biomarker for the clinical diagnosis and treatment of SSc.